Types and Abundance of Microplastics in the Digestive Tract of Cucumbers in Banyak Island, Aceh Singkil - Lianda, Desi; Suriani, Mai; Kusumawati, Ika; Lubis, Friyuanita; Dewinta, Astrid Fauzia (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2024)
Banyak Island is an island located in Aceh province, precisely in Aceh Singkil district. The people of Banyak Island often consume food whose packaging is made of plastic, and then it ends up in the sea. Island community waste thrown into the sea will enter and potentially pollute the marine ecosystem and the biota within it. This research aims to identify the type of composition and abundance of microplastics found in the digestive tract of sea cucumbers on Banyak Island, Aceh Singkil, in terms of the shape and abundance of microplastics. The method used in this research is a descriptive analysis method, which is based on photos taken with a microscope. Based on the research results, the species composition ranged from 50-114 particles/g, and the abundance of microplastics obtained was 0.2-11.4 particles/g. It was dominated by microplastic pellets, fibers, and films, with the pellet type being the first. Judging from the large amount of microplastic content found in the digestive tract of sea cucumbers on Banyak Island, Aceh Singkil, they can be categorized into types of sea cucumbers that are still suitable for consumption and sale, but if done continuously, can trigger the growth of if done frequently and over a long period, it will cause adverse effects for humans who consume it